Effect of Short-Term Anoxia on Weight Loss and Pigments of Carambola Fruit Cv.See-Thong - Prakaidao Yingsanga; Supansa Kongpakdee; Chairat Techavuthiporn; Thanwalee Srinon; Pongphen Jitareera; Lada Mathurasa (My University, 2024)
The effect of a short-term anoxia may induce stress, which can prolong the good qualities of fresh produce after harvest. The objective of this research was to study the effects of a short-term anoxia (0; control, 12, 24 and 36 h) on weight loss, chlorophyll a (Ca), chlorophyll b (Cb) and carotenoids content of carambola fruit cv. See-Thong. Collected data were analyzed for 2-day intervals during storage at 25±2 °C 60-70%RH up to 8 days. The results showed that short-term anoxia treatment could help retarding weight loss, as well as Ca, and Cb degradations. Treatment of short-term anoxia showed best results at 24 h, followed by 36 h, 12 h, and control, respectively. There was no significant difference between the anoxia treatments and the control at 8 days of storage. Carotenoid content tended to increase all treatments especially in the control, followed by anoxia treatments of 12 h, 36 h, and 24 h, respectively. Therefore, a short-term anoxia treatment at the appropriate time can help maintaining carambola fruit cv. See-Thong after harvest.
Keywords: Plant responses to water stress